Performance Analysis of Simple Aircraft in Increasing Energy Efficiency - Muslichah, Ajeng Dafiq; Sabila, Thifan Arel; Widyawati, Ratna; Kurniawati, Wahyu (Sean Institute, 2024)
This research aims to analyze the performance of simple aircraft in increasing energy efficiency. Simple airplanes are one example of a simple machine used to convert force into useful energy. In this study, we conducted a series of experiments to measure various factors that influence the efficiency of a simple aircraft, including tilt angle, arm length, and applied load. The results of this research provide important information about how we can improve the efficiency of simple aircraft and optimize energy use in everyday applications.